A Quantitative Analysis of Tunneling Current in A MOS Cell for A Low-Voltage Microcontroller - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
The tunneling current density in a MOS cell for a low-voltage microcontroller based on EEPROM is calculated for high electric strengths. Furthermore, this current density is discussed in terms of the oxide thickness and an approximate expression for the velocity of charge carriers is derived.